1994
DOI: 10.1002/jcb.240540107
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the two VEGF receptors flt and KDR in placenta and vascular endothelial cells

Abstract: Vascular endothelial growth factor (VEGF) is a newly identified growth and permeability factor with a unique specificity for endothelial cells. Recently the flt-encoded tyrosine kinase was characterized as a receptor for VEGF. A novel tyrosine kinase receptor encoded by the KDR gene was also found to bind VEGF with high affinity when expressed in CMT-3 cells. Screening for flt and KDR expression in a variety of species and tissue-derived endothelial cells demonstrates that flt is predominantly expressed in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 47 publications
5
103
0
1
Order By: Relevance
“…However, the importance of VEGFR-1 in angiogenesis was established through transgenic mouse studies in which homozygous knockout of VEGFR-1 produced early embryonic death characterized by disorganized blood vessels and endothelial cell overgrowth (Fong et al, 1995). More recent studies have confirmed the importance of VEGFR-1 in a variety of normal cells, where it has been shown to regulate monocyte migration (Barleon et al, 1996;Clauss et al, 1996), recruitment of endothelial cell progenitors (Lyden et al, 2001), increases in the adhesive properties of natural killer cells (Chen et al, 2002), and induction of growth factors from liver sinusoidal endothelial cells (LeCouter et al, 2003). Other studies have shown VEGFR-1 to be expressed on tumor cells and have implicated it in tumor growth and progression (von Marschall et al, 2000;Masood et al, 2001;La Rosa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the importance of VEGFR-1 in angiogenesis was established through transgenic mouse studies in which homozygous knockout of VEGFR-1 produced early embryonic death characterized by disorganized blood vessels and endothelial cell overgrowth (Fong et al, 1995). More recent studies have confirmed the importance of VEGFR-1 in a variety of normal cells, where it has been shown to regulate monocyte migration (Barleon et al, 1996;Clauss et al, 1996), recruitment of endothelial cell progenitors (Lyden et al, 2001), increases in the adhesive properties of natural killer cells (Chen et al, 2002), and induction of growth factors from liver sinusoidal endothelial cells (LeCouter et al, 2003). Other studies have shown VEGFR-1 to be expressed on tumor cells and have implicated it in tumor growth and progression (von Marschall et al, 2000;Masood et al, 2001;La Rosa et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular signaling leads to endothelial cell activation, including upregulation of degradative enzymes, induction of vascular permeability, and enhanced survival mechanisms (Shaheen et al, 2001;Chen et al, 2002;Patel et al, 2003). VEGFR-1 has been associated with cell migration (Barleon et al, 1996), whereas VEGFR-3 is typically associated with lymphangiogenesis in adults (Irrthum et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, infected cells release signals that stimulate other endothelial cells to participate in capillary formation. Although most types of cells produce VEGF, endothelial cells in general transcribe the gene at very low levels in contrast to other cells (Barleon et al, 1994;Dvorak et al, 1999). This fact might explain why HUVECs, in contrast to EA.hy 926 and HeLa cells, do not respond with increased VEGF expression upon co-cultivation with B. henselae.…”
Section: Discussionmentioning
confidence: 99%
“…KDR and Flt-1 are only 37% and 45% homologous in their extracellular and kinase domains, respectively 52 . Mutational mouse studies of VEGF receptor genes have shown that Flk-1, the mouse homologue of KDR, is important for endothelial cell differentiation, whereas Flt-1 is required for organization of blood vessels 53,54 .…”
Section: Vegf Receptorsmentioning
confidence: 99%
“…Monocytes express the VEGF receptor Flt-1 and respond chemotactically to VEGF 52 . Once recruited to the tissue, macrophages induce angiogenesis, in part by releasing TNF-α, which may in turn induce VEGF expression in keratinocytes and fibroblasts [92][93][94] .…”
Section: Early Cells In a Healing Wound Synthesize And Release Vegfmentioning
confidence: 99%